Metformin regulates stromal-epithelial cells communication via Wnt2/β-catenin signaling in endometriosis. (15th September 2015) - Zhang, Hui; Xue, Jing; Li, Mingjiang; Zhao, Xingbo; Wei, Deying; Li, Changzhong
Abstract: In previous studies, we found that endometriotic stromal cells lose the ability to regulate cell survival signaling in endometriotic epithelial cells. Here, we invested the effect of Metformin on the stromal-epithelial cells crosstalk in endometriosis and explored the pathway that might be involved. We found that ectopic endometriotic stromal cells (ESC) expressed and secreted higher Wnt2 protein compared with normal endometrial stromal cells (NSC). Conditioned medium (CM) from ESC supplemented with Wnt2 antibody significantly inhibited the growth of normal endometrial epithelial cells (NEC), while CM from ESC per se showed no significant effect on the growth of NEC. Metformin decreased the expression and secretion of Wnt2 in ESC. CM from Metformin-pretreated ESC significantly inhibited the growth of NEC. In conclusion, Wnt2/β-catenin signaling was involved in stromal-epithelial cells interaction in endometriosis. Metformin might regulate the stroma-epithelium communication via Wnt2-mediated signaling in endometriosis. Highlights: Increased Wnt2 expression and secretion were present in ectopic endometriotic stromal cells. Wnt2 signaling was involved in stromal-epithelial cells interaction in endometriosis. Metformin regulate the stroma-epithelium communication via Wnt2 signaling in endometriosis.